A Multidisciplinary inspection of Dental Photography: What Do Dentist Think and What Can Designer Do?. (28th July 2017) - Altiparmakogullari, Yener; Cifter, Muhsin; Cifter, Abdusselam Selami
Abstract: Dental photography, which is used in various stages of orthodontic treatment processes, is an overall system containing several components such as a camera and various retractors, mirrors or contrasts and other products. To provide an efficient photography procedure, usually more than one attendant -and sometimes even the patient himself- are required to take part. The relevant literature mostly focuses on equipment-based problems and their affects in the quality of final pictures; however, no prior research has been identified regarding the ergonomics and human factors aspects, as well as its emotional influences on the patients. In this paper, 12 professionals with at least two years of experience in dental photography are observed during the digital dental photography procedure, and semi-structured interviews are conducted with them. The identified shortcomings provide hints for possible areas of improvement regarding the equipment used in the process and the overall system.